Nanomaterials in Rheumatoid Arthritis Over Two Decades: A Bibliometric Study of Inflammatory Pathways and Emerging Therapeutic Strategies - Muhammad Amin Nasution; Muhammad Andry; Nia Novranda Pertiwi; Hindri Syahputri; Syilvi Rinda Sari; Aqmal Ramadhan Pasaribu (Postgraduate, University of Mataram, 2026)
The rapid expansion of nanomaterial-based rheumatoid arthritis (RA) research has produced a fragmented body of literature, limiting clear recognition of major journals, influential contributors, collaboration patterns, and shifting research priorities. This study presents a two-decade bibliometric mapping of nanomaterials in RA with an inflammation-focused perspective. English-language publications from 2005 to 2025 were collected from Scopus using a nanomaterial–RA–inflammation search strategy, yielding 5,110 initial records. Data were refined in OpenRefine through deduplication, author-name harmonization, and keyword normalization. Following eligibility screening, 720 articles were retained for core bibliometric analysis. Biblioshiny, supported by the Bibliometrix R package, was used to measure annual publication trends, productive sources, leading authors, institutional output, and collaborative networks. Conceptual development was assessed through keyword co-occurrence analysis and thematic mapping, with network visualizations generated in VOSviewer. Results indicate accelerated publication growth in the recent period, with outputs concentrated in drug delivery and biomaterials-related journals. Scientific productivity was driven by a limited group of countries and institutions, reflecting hub-based knowledge production. Keyword and thematic analyses identified targeted drug delivery and macrophage polarization as motor themes, while PI3K–AKT and Hedgehog signaling emerged as developing topics. Overall, the field shows rapid growth and organized thematic evolution.